Age-related changes in auditory temporal processing in the rat - Suta, Daniel; Rybalko, Natalia; Pelánová, Jana; Popelář, Jiří; Syka, Josef (Experimental gerontology, 2011)
Presbycusis, as the deterioration of hearing ability occurring with aging, can be manifested not only in a shift of hearing thresholds, but also in a deterioration of the temporal processing of acoustical signals, which may in elderly people result in degraded speech comprehension. In this study we assessed the age-related changes in the temporal processing of acoustical signals in the auditory system of pigmented rats (Long Evans strain). The temporal resolution was investigated in young adult (3-4 months) and old (30-34 months) rats by behavioral and electrophysiological methods: the rats' ability to detect and discriminate gaps in a continuous noise was examined behaviorally, and the amplitude-rate function was assessed for the middle latency response (MLR) to clicks. A worsening of the temporal resolution with aging was observed in the results of all tests. The values of the gap detection threshold (GDT) and the gap duration difference limen (GDDL) in old rats increased about two-fold in comparison with young adult rats. The MLR to a click train in old rats exhibited a significantly faster reduction in amplitude with an increasing stimulation rate in comparison with young adult rats. None of the age-related changes in the parameters characterizing temporal resolution (GDT, GDDL and MLR to a click train) correlated with the degree of the age-related hearing loss. However, the age-related changes in MLR amplitude-rate function correlated with the age-related changes in GDDL, but not with the changes in GDT. The behavioral and electrophysiological data clearly show that aging in rats is accompanied with a pronounced deficit in the temporal processing of acoustical signals that is associated with the deteriorated function of the central auditory system.
Keywords: Discrimination Learning; Auditory Threshold; Aging; Rats, Long-Evans; sluchové evokované potenciály; Presbycusis; diskriminační učení; akustická stimulace; sluchový práh; krysa rodu Rattus; Evoked Potentials, Auditory; Animals; ženské pohlaví; zvířata; Acoustic Stimulation; Rats; stárnutí; potkani Long-Evans; Female; presbyakuze